Growth, Development And Productivity Of Various Varieties Of Winter Wheat Under Extreme Conditions - Sadykov E.P; Bekbanov B.A; Matniyazova A.T; Polatov N.E (Zien Journals, 2023)
The study found that the differences in the yield of winter wheat varieties caused by weather conditions are much greater than by agrotechnical factors (fertilizer rates, timing and methods of sowing, variety, etc.). At the same time, weather conditions are understood as air temperature and humidity, photosynthetic active radiation and carbon dioxide concentration.
Keywords: Variety; Specimen; Plastic Variety; Frost Resistance